MAP2K1 Mutation in Zebrafish Endothelial Cells Causes Arteriovenous Shunts Preventable by MEK Inhibition - Christopher L. Sudduth; Nicola Blum; Patrick J. Smits; Yu Sheng Cheng; Matthew P. Vivero; Matthew P. Harris; Nathan D. Lawson; Arin K. Greene (Journal of Vascular Anomalies, 2023)
Objectives:. Arteriovenous malformation (AVM) is a congenital lesion with a nidus of irregular blood vessels connecting arteries to veins instead of a normal capillary bed. Somatic MAP2K1 activating mutations in endothelial cells cause extracranial AVM. The purpose of this study was to create a MAP2K1 AVM animal model using zebrafish and to test pharmacotherapy. Methods:. Single-cell casper Tg(gata1a:DsRed) zebrafish embryos were injected with plasmid DNA (control [pTol2-Fli:GFP]; mutant [pTol2-Fli:GFP-kdrl:MAP2K1K57N]) and Tol2 transposase mRNA to mosaically express activated MAP2K1 in endothelial cells. Two cohorts of fish were examined: group 1 (n = 161) established phenotypes and group 2 (n = 126) tested MEK inhibition. Blood flow was visualized using DsRed fluorescence of erythrocytes. Embryos were imaged 72 hours postfertilization. Results:. Group 1 exhibited abnormal arteriovenous shunts in 58 of 96 (60%) embryos expressing MAP2K1K57N in endothelial cells. Shunts occurred between the proximal aorta and common cardinal vein (n = 39; 67%) or between the major artery and vein within the trunk or tail (n = 19; 33%). Shunts were not present in control zebrafish (n = 65). MEK inhibition reduced shunt frequency caused by endothelial MAP2K1K57N expression in group 2 from 84% to 55% (0.2 μM) or 25% (0.4 μM) (P = .006). Conclusions:. Zebrafish endothelial cells expressing mutant MAP2K1 form abnormal arteriovenous shunts supporting the causality of the variant in human AVMs. MEK inhibition reduced shunt formation validating its potential efficacy as a pharmacotherapeutic option for AVM. This zebrafish model may be used for further study of the etiopathogenesis of AVM as well as to test drugs.